Asymmetric Sequential Cu‐Catalyzed 1, 6/1, 4‐Conjugate Additions of Hard Nucleophiles to Cyclic Dienones: Determination of Absolute Configurations and Origins of Enantioselectivity. Issue 31 (16th May 2017) - Blons, Charlie; Morin, Marie S. T.; Schmid, Thibault E.; Vives, Thomas; Colombel‐Rouen, Sophie; Baslé, Olivier; Reynaldo, Thibault; Covington, Cody L.; Halbert, Stéphanie; Cuskelly, Sean N.; Bernhardt, Paul V.; Williams, Craig M.; et al.
Abstract: The first stereocontrolled Cu‐catalyzed sequential 1, 6/1, 4‐asymmetric conjugate addition (ACA) of C‐metalated hard nucleophiles to cyclic dienones is reported. The use of DiPPAM (diphenylphosphinoazomethinylate) followed by a phosphoramidite as the stereoinducing ligands facilitated both high ee values for the 1, 6‐ACA and high de values for the 1, 4‐ACA reaction components, which thus gave enantioenriched 1, 3‐dialkylated moieties. The absolute configurations were determined by using vibrational circular dichroism (VCD) and optical rotatory dispersion (ORD) spectroscopy, in combination with DFT calculations and X‐ray analysis. Interestingly, DFT calculations for the mechanism of enantioselective 1, 6‐addition by using an unprecedented Cu–Zn bimetallic catalytic system confirmed this attribution. Lastly, exploring intramolecular cyclization avenues for enantioenriched 1, 3‐dialkylated products provided access to the challenging drimane skeleton. Abstract : Taking control : A stereocontrolled Cu‐catalyzed sequential 1, 6/1, 4‐asymmetric conjugate addition (ACA; see scheme) of C‐metalated hard nucleophiles to cyclic dienones is reported. High ee and de values were reached to give enantioenriched 1, 3‐dialkylated moieties. The absolute configurations were determined by using vibrational circular dichroism (VCD) and optical rotatory dispersion (ORD) spectroscopy, in combination with DFT calculations and X‐ray analysis.